Concentration of heavy metals in spring waters of Kochani and their impact on human health - Serafimova Mijalova, Emilija; Tortevska Danilov, Elena; Pendevski, Vasil; Zhivikj, Zoran; Petrushevska tozi, Lidija; Petreska ivanovska, Tanja (Macedonian Pharmaceutical Association, 2022)
The concentration of lead (Pb), cadmium (Cd), aluminium (Al), manganese (Mn), and iron (Fe) in spring waters in the vicinity of Kochani was investigated to ascertain the health risk exposure. Heavy metal water contamination is possible mostly due to wrongful human activities either industrially or residentially and exposure to toxic doses of heavy metals can cause acute and chronic diseases. To examine heavy metal contamination of spring waters as well as possible seasonal variations, water samples in two seasons, autumn 2021 and spring 2022 were collected. For this aim, ten locations within the area of Kochani were selected. The spring water samples were collected directly from the source or from the catchment that was made. The samples were collected in appropriate bottles, previously washed with detergent and rinsed with distilled water. The examination of heavy metals was carried out immediately after sampling using UV spectrophotometric method, with an absorption spectrum of 190-1100 nm. The results have revealed no major deviations from the maximum concentrations allowed for Pb, Cd, Al, Mn, and Fe defined within the Official Guidelines in the Republic of North Macedonia, except moderately increased levels of lead in two samples during autumn season and manganese in four samples in the spring season 2022. Key words: heavy metal levels, spring water, UV spectrophotometry, human health